Synthesis and Biological Evaluation of 9-alkoxy-6,7-dihydro-5H-benzo[c] [1,2,4]triazolo[4,3-a]azepines as Potential Anticonvulsant Agents - Piao, F.-Y.; Peng, B.; Zhang, W.-B.; Zhang, W.; Han, R.-B. (Arzneimittelforschung, 2012)
A novel series of 9-alkoxy-6,7-dihydro-5H-benzo[c][1,2,4]triazolo[4,3-a]azepine derivatives was synthesized and screened for anticonvulsant activity by the maximal electroshock (MES) test and the subcutaneous pentylenetetrazol (scPTZ) test. Neurotoxic effects were also determined by the rotarod neurotoxicity test. The results revealed that all of the compounds exhibited anticonvulsant activity, Compound 5d was found to possess the most potential anticonvulsant activity in the anti-MES potency test; it had a median effective dose (ED50) of 12.3 mg/kg, a median toxicity dose (TD50) of 73.5 mg/kg, and a protective index (PI) of 6.0, which is slightly lower than the PI of the prototype drug carbamazepine (ED50=8.8, PI=8.1). In the scPTZ test, compound 5c was the most active, with an ED50 value of 19.8 mg/kg, a TD50 value of 80.8 mg/kg and a PI value of 4.1, which are much greater than the ED50 and the PI of the prototype drug carbamazepine (ED50>100, PI<0.72), Possible structure-activity relationships are also discussed.
Keywords: benzotriazoloazepine; synthesis; anticonvulsant activity